Long-Term Response to Gemcitabine, Cisplatin, and Nab-Paclitaxel Followed by Maintenance Therapy for Advanced Gallbladder Cancer: A Case Report and Literature Review - Liu, Ting; Li, Qing; Zhang, Wenjie; Zhu, Qing (Frontiers in Oncology, 2021)
Abstract Background: Gallbladder cancer (GBC) is the most common and devastating tumor type of biliary tract cancer (BTC) with poor outcomes. A new combined regimen of gemcitabine, cisplatin plus nab-paclitaxel has been regarded as an effective option for patients with advanced BTC in a phase II trial. In addition, maintenance therapy after first-line treatment has been shown to improve disease control rate of various solid tumors but not been mentioned in GBC patients. Seminar we reported a metastatic GBC patient who treated with the triple drug regimen followed by maintenance therapy of capecitabine or S-1 and achieved long-term survival benefit. Case presentation: A 68-year-old man was diagnosed with gallbladder adenocarcinoma with liver, supra-diaphragmatic and abdominal lymph nodes metastases (cT3N2M1, stage IVB). Partial response (PR) was attributed to him after 5 cycles of gemcitabine and cisplatin chemotherapy. Further 3 cycles of nab-paclitaxel plus gemcitabine-cisplatin regimen yielded him a complete response of all tumor lesions. Subsequent administration of maintenance therapy with capecitabine followed by S-1 achieved a disease-free survival of 11 months for the patient. Moreover, the patient remained effective with this triple drug regimen when the disease re-progressed, achieving PR after two cycles of chemotherapy. Overall, the treatment regimens were well tolerated with no grade 3 or higher adverse effects occurring. Notably, the serum carbohydrate antigen 199 (CA199) levels were closely related to the treatment response and increased before the lesions were found on PET-CT during follow-up. Conclusion: Our findings suggest that adding nab-paclitaxel into gemcitabine-cisplatin regimen may result in a favorable efficacy in patients with advanced GBC. Further maintenance therapy with capecitabine or S-1 after first-line therapy appears to be a reasonable option for these patients, and it is valuable to monitor CA199 levels during treatment and follow-up.